Melatonin promotes sorafenib‐induced apoptosis through synergistic activation of JNK/c‐jun pathway in human hepatocellular carcinoma. Issue 3 (6th March 2017) - Lin, Shibo; Hoffmann, Katrin; Gao, Chao; Petrulionis, Marius; Herr, Ingrid; Schemmer, Peter
Abstract: Melatonin has been shown to exert anticancer activity on hepatocellular carcinoma (HCC) through its antiproliferative and pro‐apoptotic effect in both experimental and clinical studies, and sorafenib is the only approved drug for the systemic treatment of HCC. Thus, this study was designed to investigate the combined effect of melatonin and sorafenib on proliferation, apoptosis, and its possible mechanism in human HCC. Here, we found that both melatonin and sorafenib resulted in a dose‐dependent growth inhibition of HuH‐7 cells after 48 hours treatment, and the combination of them enhanced the growth inhibition in a synergistic manner. Colony formation assay indicated that co‐treatment of HuH‐7 cells with melatonin and sorafenib significantly decreased the clonogenicity compared to the treatment with single agent. Furthermore, FACS and TUNEL assay confirmed that melatonin synergistically augmented the sorafenib‐induced apoptosis after 48 hours incubation, which was in accordance with the activation of caspase‐3 and the JNK/c‐jun pathway. Inhibition of JNK/c‐jun pathway with its inhibitor SP600125 reversed the phosphorylation of c‐jun and the activation of caspase‐3 induced by co‐treatment of HuH‐7 cells with melatonin and sorafenib in a dose‐dependent manner. Furthermore, SP600125 exhibited protective effect against apoptosis induced by the combination of melatonin and sorafenib. This study demonstrates that melatonin in combination with sorafenib synergistically inhibits proliferation and induces apoptosis in human HCC cells; therefore, supplementation of sorafenib with melatonin may serve as a potential therapeutic choice for advanced HCC.